Evaluation of the effect of Rimsulfuron and Linuron on weed infestation and potato yield - B, Hajjaj; A, El Oualkadi (International Journal of Environment, Agriculture and Biotechnology, 2019)
A potato weeding trial was conducted during the 2017 growing season. The purpose of this experimentation is to evaluate the effect on weed infestation and impact on potato yield of tow herbicides: Linuron as preemergence herbicide and Rimsulfuron as postemergence herbicide. Results showed that the best potato yields are obtained by treatments that gave the best weed control. Linuron with a rate of 187.5 g/ha has shown excellent efficacy exceeding 93% of weed control and giving yields exceeding 46.3 tons / ha. Treated plots with Rimsulfuron at 15 g/ha gave in average 78% of weed control and may be recommended when the pre-emergence weed treatment is missed.